(untitled) (Research, Society and Development, 2025)
Considering that poultry farming is one of the main businesses in the country’s agricultural sector, guaranteeing Brazil the title of largest exporter of chicken meat, it is of great importance that measures are adopted to prevent the entry of possible pathogens and cause, in addition to health problems in animals, economic problems for the state and even for the country, since some diseases are zoonotic. In this sense, the present study aimed to evaluate poultry farms producing broiler chicken, from three different integrators, regarding compliance with mandatory biosecurity measures. The evaluation was carried out using a checklist in accordance with Normative Instruction No. 56. The results showed that of the 15 farms evaluated, 10 were unfit for housing, the measures with the highest percentage of disagreement were related to failure in the sealing and size of the composter (66.67%), ineffective isolation fence (60%), outdated anti-bird screen (53.33%), presence of cracks/holes/bird nests (46.67%), water chlorination register not filled out (46.67%) and bait holders not distributed according to the map (33.33%). It was concluded that some biosecurity measures require greater attention from everyone involved in the broiler chicken raising process, to continue strengthening the success of the sector.